The neuropeptidome of Carabus (Coleoptera, Adephaga: Carabidae). (March 2020) - Ragionieri, Lapo; Predel, Reinhard
Abstract: Neuropeptides are signaling molecules involved in the regulation of virtually all physiological functions of Metazoa. In insects, more than 50 neuropeptide genes can be present in a single species, and thus neuropeptidergic systems are attractive targets for the development of environmentally friendly pesticides. Such approaches require not only knowledge of the neuropeptidomes of pests, but also detailed knowledge of the corresponding systems in beneficial insects. In Coleoptera, there is no profound knowledge of the neuropeptides in the adephagan lineage, which contains many of the ecologically important predators of caterpillars. We analyzed by transcriptomics, mass spectrometry and immunohistochemistry the neuropeptidomes of the two Carabus species C. violaceus and C. problematicus . This information, which contains detailed data on the differential processing of CAPA peptides, allows for the recognition of features typical only of the polyphagan lineage with its many pests. The neuropeptidomics data, which also confirmed the processing of a number of protein hormones, represent the highest number of neuropeptides that have been identified so far from Coleoptera. The sequences of the mature neuropeptides of the two Carabus species, whose ancestors separated about 13 Mya, are highly similar and no sequence substitutions were found in single-copy neuropeptides. Graphical abstract: Image 1 Highlights: First neuropeptidomes of adephagan beetles were elucidated using transcriptomics and mass spectrometry. Data on presence and distribution of neuropeptides provide the currently most comprehensive dataset known from beetles. Differential processing of CAPA peptides leads to cell-specific inactivation of neuropeptides. Specific features of neurohemal release sites of FMRFamides and CAPA peptides were identified using immunochistochemistry. The comparison of neuropeptides of the two distantly related Carabus species revealed very low differentiation.